Water Resources Management in Small Islands: A Review of Public Policy Implementation in the Development of Nomaha Reservoir, Kisar Island - Rumihin, Ony Frengky (Baileo: Jurnal Sosial Humaniora, 2024)
This article explores the implementation of public policy in water resources management on small islands, focusing on the development of the Nomaha Reservoir on Kisar Island, Maluku. The study aims to provide a comprehensive understanding of how water scarcity can be addressed through a synergistic approach that integrates technical, policy, and sociocultural dimensions. Employing a mixed-methods design, the research combines technical feasibility assessments, policy analysis through document reviews, and field observations of the island’s topographic, hydrological, and environmental characteristics. The findings reveal that the Nomaha Reservoir project reflects a strategic response to water scarcity, supported by spatial planning regulations at the national, provincial, and district levels. The study highlights the importance of local community participation in water management efforts, showing increased public awareness, behavior change in water use, and the incorporation of local wisdom—particularly the customary environmental regulation known as Sasi. The novelty of this study lies in its integration of engineering solutions with policy frameworks and indigenous practices, offering a model for sustainable water governance in small island contexts. This article contributes to the social sciences and humanities by emphasizing the value of participatory, multi-level, and culturally grounded approaches to environmental management, particularly in geographically and ecologically vulnerable regions.